Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

We set (as usual) $\displaystyle{x \choose k} := \frac{x \cdot (x-1) \cdots (x-k+1)}{k!}$ for $x\in \mathbb{C}$.

Now we can define a function

$\displaystyle f(x) := \sum\limits_{k=0}^\infty {x \choose k}$.

Does anybody know how this function is called (I need its name, so that I can get more information about it)? I believe, it should be well-known, but I don't know its name.

Note that if we defined $\displaystyle{x \choose k} := \frac{x^k}{k!}$ instead, we would simply get the $\exp$ function - so my function is probably be related to it.

share|cite|improve this question
How sure are you that the sum even converges for non-integral $x$? The series for the exponential function converges because the $k$ factors in the denominator of each term eventually dominate the $x$ factors in the numerator -- but here we eventually get factors of $-(k+1-x)$ in the numerator, which grow in magnitude as $k$ does. So it is not obvious even that $\binom xk\to 0$. – Henning Makholm Jan 22 '12 at 20:47
The series certainly doesn't converge for $x \le -1$. @aelguindy: you need the stronger result that the numerator is less than $|x|^k$ in absolute value, which is false. – Qiaochu Yuan Jan 22 '12 at 20:52
You're right, comment removed. – aelguindy Jan 22 '12 at 20:56
Nubok, are you familiar with the binomial theorem for non-integer exponents, in the form of an expansion of the expression $(1+a)^x$? I'd suggest you start there. – Gerry Myerson Jan 22 '12 at 22:15
Note $f(0)=1$ (the empty product is multiplicative unity) and $$f(x+1)=1+\sum_{k=1}^\infty\binom{x+1}{k}=1+\sum_{k=0}^\infty\left[\binom{x}{k}‌​+\binom{x}{k+1}\right]=2f(x).$$ That's a good hint $f(x)=2^x$. – anon Jan 23 '12 at 3:04

By Binomial theorem, we have $$\sum\limits_{k=0}^\infty {x \choose k} a^k b^{x - k} = (a + b)^x.$$ Substituting $a = b = 1$, we have $f (x) = 2^x$, if we define $f : N \mapsto N$, that is, at the positive integer values of $x$.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.